Deprotonated curcumin as a simple and quick available natural dye for dye sensitized solar cells. Issue 2 (17th January 2016) - Yoon, S. J.; Lim, I.; Kim, J. H.; Adhikari, S.; Lee, W. Y.; Lee, J. K.; Shrestha, N. K.; Ahn, H.; Han, J. W.; Han, S.-H.
Abstract: In the present study, deprotonation of curcumin dye using potassium carbonate was performed successfully, which produced fairly stable deprotonated dye with a large bathochromic shift in the visible light absorption spectrum. The light-harvesting efficiency of this deprotonated dye was investigated in TiO2 -based dye sensitized solar cells, which exhibited an energy conversion efficiency of 0.91%, and this value is 8.3 times higher than that of the dye sensitized solar cells with curcumin photosensitizer without deprotonation.